Does Pyloric Drainage Have a Role in the Era of Minimally Invasive Esophagectomy? - Nobel, Tamar (Surg Endosc, 2018)
INTRODUCTION: Pyloric drainage during minimally invasive esophagectomy (MIE) may be more technically challenging than during the open approach and alternatives to the classic surgical drainage approach have increased in popularity. However, data are lacking to demonstrate whether one technique is superior in MIE. The purpose of this study was to compare postoperative outcomes after MIE between different pyloric drainage methods. METHODS: We performed a retrospective review of a prospectively maintained database of patients undergoing MIE at a single academic institution. Patients were divided into three groups for analysis: no drainage, intrapyloric Botulinum Toxin injection, and surgical drainage (pyloroplasty or pyloromyotomy). The primary outcome was any complication within 90 days of surgery; secondary outcomes included reported symptoms and need for pyloric dilation at 6 and 12 months postoperatively. Comparisons among groups were conducted using Kruskal Wallis RESULTS: There were 283 MIE performed between 2011 and 2017; of these, 126 (45%) had drainage (53 Botulinum injection and 73 surgical). No significant difference in the rate of postoperative complications, pneumonia or anastomotic leak was observed between groups. At 6 and 12 months, patients that received Botulinum Toxin and surgical drainage had significantly more symptoms than no drainage (p<.0001) and had higher need for pyloric dilation at 6 months (p=0.007). CONCLUSIONS: Pyloric drainage was not significantly associated with lower postoperative complications or long-term symptoms. While Botulinum injection appears safe postoperatively, it was associated with increased morbidity long-term. Pyloric drainage in MIE may be unnecessary.